Excited State Modulation for Organic Afterglow: Materials and Applications. Issue 45 (16th September 2016) - Xu, Shen; Chen, Runfeng; Zheng, Chao; Huang, Wei
Abstract : Organic afterglow materials, developed recently by breaking through the difficulties in modulating ultrafast‐decayed excited states, exhibit ultralong‐lived emission for persistent luminescence with lifetimes of several orders of magnitude longer than traditional fluorescent and phosphorescent emissions at room temperature. Their exceptional properties, namely ultralong luminescent lifetime, large Stokes shifts, facile excited state transformation, and environmentally sensitive emission, have led to a diverse range of advanced optoelectronic applications. Here, the organic afterglow is reviewed from the perspective of fundamental concepts on both phenomenon and mechanism, examining the technical challenges in relation to excited state tuning and lifetime elongation. In particular, the advances in material design strategies that afford a large variety of organic afterglow materials for a broad utility in optoelectronics including lighting and displays, anti‐counterfeiting, optical recording, chemical sensors and bio‐imaging are highlighted. Abstract : Organic afterglow with persistent room‐temperature phosphorescence (lifetime > 0.1 s) has revolutionized current understanding of organic luminescence, exhibiting promising potential in a wide range of optoelectronic applications. Recent advances in the development of organic afterglow materials are summarized, extracting fundamental principles from excited state manipulation strategies, organic afterglow phenomena and characterizations, material constructions, and device applications.